Reducing inequality by correcting misperceptions: Experimental evidence on student aid take-up - Sebastian Riedmiller (Max Planck Institute for Research on Collective Goods, 2025)
Financial student aid improves educational outcomes and reduces social inequality, yet many eligible students do not take it up. To examine whether correcting misperceptions increases take-up, I conducted an RCT with 6,225 university students across Germany who were not receiving aid. I find that 63% of students systematically underestimate the financial benefits and overestimate repayment obligations of student aid, and 86% misperceive their eligibility. Providing combined information about the program conditions and individual eligibility significantly corrected misperceptions after six months and increased take-up by 46% after one year. This increase is particularly strong among disadvantaged students. After take-up, students report higher available income while reducing earnings and parental support. These findings suggest that correcting misperceptions can reduce social inequality by alleviating financial constraints among disadvantaged students and their parents.
hdl:21.11116/0000-0011-861F-4
Keywords: C93; D14; D83; D90; H52; I22; 330; student aid; misperceptions; field experiment; social inequality; BAföG